Performance Analysis of Sharia Banking in Indonesia: Abu Zahrah Maqasid Shariah Index Approach - Eko Suprayitno; Yunan Syaiful Haq (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
This study aims to analyze the performance of Islamic Banking (IB) in Indonesia through the maqashid shariah index Abu Zahrah approach. Performance appraisal on Islamic Banking (IB) is generally done through financial performance measurements without including non-financial performance measurements.  Furthermore, this study uses descriptive quantitative research methods, namely an approach with a ratio value that can be calculated and described. The research object is 3 Islamic banks in Indonesia registered on the Indonesia Stock Exchange (IDX) and published their financial reports for 2018-2020. The results showed that Panin Dubai Sharia Bank obtained the best MSI score among 2 other Islamic banks with an MSI value of 38.59%. Furthermore, Bank BRI Sharia with an MSI score of 30.38%, and finally Bank BTPN Sharia with an MSI score of 30.24%. Panin Dubai Sharia Bank is more focused on achieving maqashid sharia aspects than the other 2 Islamic banks.